If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -28 = -22 + 9p Reorder the terms: -28 + 8p = -22 + 9p Solving -28 + 8p = -22 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -28 + 8p + -9p = -22 + 9p + -9p Combine like terms: 8p + -9p = -1p -28 + -1p = -22 + 9p + -9p Combine like terms: 9p + -9p = 0 -28 + -1p = -22 + 0 -28 + -1p = -22 Add '28' to each side of the equation. -28 + 28 + -1p = -22 + 28 Combine like terms: -28 + 28 = 0 0 + -1p = -22 + 28 -1p = -22 + 28 Combine like terms: -22 + 28 = 6 -1p = 6 Divide each side by '-1'. p = -6 Simplifying p = -6
| 1000000+1=x | | 32x+8y=5600 | | 5(2m-5)=7-(m+3) | | -5a+6a=-10+3a | | 432=x(x-6)(x-6) | | -5p+8+6p=10 | | x+3x=4x | | .5x-1.5=-6.5 | | (180x-1800)/(x)(x-20) | | 3x-45-3x= | | x=5/8y | | Y^2+9=6y | | 38=0.4n | | 3n+2+1=-21 | | 7+(4+4)= | | 0.3x=26 | | x1/10 | | 11=x-5+8 | | 3n+2+1=-2 | | x(x-6)(x-2)=996 | | 49w=-8 | | 8(x-2)=2x+8 | | 15t-14=-14 | | 9=-5r-4r | | -1(x-6)= | | 8x^2+2x+9=0 | | -9(6n+4)=18-5n | | 2(6x+6)= | | 2=4k-5k | | 8a+24=-16 | | 25+q=0.5-3 | | 6x+-1+5x= |